Ekonomia narodowa a etyka w ujęciu Stanisława Głąbińskiego - Szymański, Zdzisław (Annales. Etyka w Życiu Gospodarczym, 2014)
Stanisław Głąbiński (1862-1941), professor of Lviv University and the author of the two-volume ‘National Economics (‘Ekonomika narodowa’), was one of the main representatives of the historical-national approach in Polish economics. The study of national economics which he created was divided into general economics, i.e. economic theory, and practical economics, referred to as economic and social policies. Głąbiński emphasizes that there is a close relationship between the latter and ethics. Before the development of economic theory, economic thought was normative, because of its close relationship to ethics. However, it was not the history of economic theory, but the history of the notion of economic politics and of its practical application. Due to the social nature of ethics, there are also specific relations between it and theoretical economics. In modern countries finding a solution to the so-called social question has become a common task of economics and ethics. Ethical topics are also contained in the content of the category ‘social resources’, in which the social determinants of human economic activity find their fullest reflection. This applies in particular to the category of moral resources, which illustrates the functioning of state bodies and public institutions, the state of education, the prevailing habits and the customs and the character of the nation.